Should We All Be Moral Saints? - Skácelová, Anna (Univerzita Pardubice, 2019)
This thesis is concerned with the term "moral saint". Three interpretations of the term are discussed - one definition is from Raimond Gaita and two are from Susan Wolf. Gaita´s moral saint reveals the value of those who have their humanity obscured through loving treatment. Wolf´s moral saints are people who try to behave as morally well as possible, either because the happiness of others makes them happy or because they disregard their own happiness completely. These three concepts are elaborated and critiqued in order to answer the question whether we should try to be like them.
Měli bychom být morálními světci?
Keywords: filosofie; analytická filosofie; etika; Gaita, Raimond; Wolf, Susan; morální světec; morální svatý; philosophy; analytic philosophy; ethics; Gaita, Raimond; Wolf, Susan; moral saint